2017
DOI: 10.1111/grs.12170
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the short‐term intake rate of herbage by heifers grazing annual grasses throughout the growing season

Abstract: Annual temperate grasses go through abrupt changes in morphological composition during the growing season, which can affect ingestive behavior of grazing cattle. However, few studies have examined the effects of gradual structural changes in annual temperate pastures on the herbage intake rate during the growing season. We hypothesized that lenient grazing (removal of 40% of the initial pre‐grazing height) maintains short‐term intake rate (STIR) of grazing cattle over the entire growing season, even with decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Structural characteristics of the forage sward can stimulate, inhibit or limit the ingestive behaviour of animals 15 17 . These structural variables include leaf length and shape, cuticle thickness, stem physical properties, tiller density, proportion of senescent material, proportion and quantity of leaf blades, all of which are dependent on the species, growth habit, height, morphogenic characteristics, life cycle and longevity of the forage plant 17 24 . Thus, in the context of competition strategy at the plant–animal interface, the animals adapt to changes found in the pasture at the time of grazing, which promote behavioural changes, such as altering the pattern of displacement, food selection, the ratio of mass acquired and rate of harvest by animals, and mandibular and non-mandibular movements 25 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Structural characteristics of the forage sward can stimulate, inhibit or limit the ingestive behaviour of animals 15 17 . These structural variables include leaf length and shape, cuticle thickness, stem physical properties, tiller density, proportion of senescent material, proportion and quantity of leaf blades, all of which are dependent on the species, growth habit, height, morphogenic characteristics, life cycle and longevity of the forage plant 17 24 . Thus, in the context of competition strategy at the plant–animal interface, the animals adapt to changes found in the pasture at the time of grazing, which promote behavioural changes, such as altering the pattern of displacement, food selection, the ratio of mass acquired and rate of harvest by animals, and mandibular and non-mandibular movements 25 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Canopy structure modifies livestock short-term ingestion capacity (Carvalho et al, 2015;Guzatti et al, 2017). The highest instantaneous intake rate in CH25/ DS0 was due to the increased bite mass associated with a faster bite rate, which can be explained by the ease of selection, apprehension, and forage intake since the upper canopy stratum was characterized by a predominance of leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in estimation of intake between the two techniques may be associated with inherent error of both methodologies. Many studies in the literature reported high interindividual variability when using the DW method (Fonseca et al., 2012; Guzatti et al, 2017; Mezzalira et al., 2017). Other sources of variation, such as differences between paddocks and shifts (a.m. vs. p.m.) also add to the compound variation for many of the methodologies used for estimating intake (Bailey et al., 1996; Fraser, 2009; Gregorini, 2012).…”
Section: Discussionmentioning
confidence: 99%